COMMUNICATIVE POTENTIAL OF SOFT POWER: SOCIO-PHILOSOPHICAL ANALYSIS - Poda, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
The article is dedicated to the analysis of soft power discourses in the context of international relations of the modern world. These discourses retain their leading significance in the symbolic space of politics, exerting a targeted influence on public consciousness. The basis of discursive influences is the modeling of attractive images of state institutions and political subjects as a prompt response to foreign policy and domestic political challenges and threats.